Time to first treatment is an independent prognostic factor for Multiple Myeloma (MM). (December 2022) - Hatic, Haris; Inselman, Shealeigh; Inselman, Jonathan; Kommalapati, Anuhya; Tella, Sri Harsha; Paludo, Jonas; Durani, Urshila; Go, Ronald S.; Goyal, Gaurav
Abstract: Introduction: Multiple myeloma (MM) is an incurable plasma cell neoplasm. In this study, we aimed to analyze the impact of time to initiation of systemic therapy for MM on overall survival (OS). Methods: We identified cases diagnosed with MM from the National Cancer Database from 2004 to 2013. Results: A total of 38, 178 MM patients were included in the analysis. The median time to systemic therapy in our cohort was 17 days (range 0–120). The median OS for patients who initiated therapy > 30-days after diagnosis was longer than those who received it ≤ 7 days (46 vs. 27-month, p < 0.001). On multivariable analysis, patients who received treatment ≤ 7 days from diagnosis had worse mortality compared with those receiving treatment > 30 days (HR 1.5; 95% CI 1.4–1.6). Conclusions: In our study, time to initiation of systemic therapy was an independent prognostic factor in MM. Similar to other lymphoid malignancies, this metric may be a surrogate for high-risk disease in MM, and future trials may need to investigate time-to-treatment as a factor to allow enrollment of potentially sick patients. Highlights: Prognostic impact of time to initiation (TTI) of therapy is unknown in multiple myeloma (MM). TTI of systemic therapy was an independent prognostic factor in MM. TTI ≤ 7 days was associated with higher overall mortality compared with > 30 days.